Correction: Will R&D make investors more tolerant? Analysis based on the performance forecast of Chinese listed companies. - Yixiao Chen; Yisu Wang; Huafeng Zhao; Wei Xu (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0280237.].